2022
DOI: 10.1128/spectrum.02842-22
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dominance by Multidrug-Resistant Bacteria in Pediatric Liver Transplant Patients

Abstract: In this study, we track the relative intestinal loads of antibiotic resistance genes among pediatric liver transplant patients and determine the relationship between this load, antibiotic consumption, and infections caused by antibiotic-resistant organisms. We demonstrate that the consumption of broad spectrum antibiotics increase this load and decrease the gut microbial diversity among these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
0
4
2
Order By: Relevance
“…They were also different from those determined for pediatric liver transplant patients that receive prolonged and repeated treatments with antibiotics ( Dahdouh et al., 2022 ). Nevertheless, in all three studies, the consumption of antibiotics was associated with intestinal RLs, where in adults the consumption of non-β-lactams and carbapenems were associated with high RLs for bla OXA-48 ( Lázaro-Perona et al., 2020 ), and additionally to bla CTX-M-1-Family and bla OXA-1 for pediatric liver transplanted patients ( Dahdouh et al., 2022 ). In contrast, this current study showed that the consumption of β-lactams and glycopeptides is associated with a lower incidence of detecting bla CTX-M-1-Family and bla OXA-1 , and the consumption of aminoglycosides and TMX with a lower incidence of detecting bla OXA-48 in the critically ill pediatric patient population.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…They were also different from those determined for pediatric liver transplant patients that receive prolonged and repeated treatments with antibiotics ( Dahdouh et al., 2022 ). Nevertheless, in all three studies, the consumption of antibiotics was associated with intestinal RLs, where in adults the consumption of non-β-lactams and carbapenems were associated with high RLs for bla OXA-48 ( Lázaro-Perona et al., 2020 ), and additionally to bla CTX-M-1-Family and bla OXA-1 for pediatric liver transplanted patients ( Dahdouh et al., 2022 ). In contrast, this current study showed that the consumption of β-lactams and glycopeptides is associated with a lower incidence of detecting bla CTX-M-1-Family and bla OXA-1 , and the consumption of aminoglycosides and TMX with a lower incidence of detecting bla OXA-48 in the critically ill pediatric patient population.…”
Section: Discussioncontrasting
confidence: 75%
“…In this study, we analyzed the intestinal RLs of the four genes of β-lactamases that are endemic at our hospital ( bla CTX-M-1-Family , bla OXA-1 , bla OXA-48 , and bla VIM ) using a previously validated qPCR assay ( Dahdouh et al., 2022 ). The %RLs of bla CTX-M-1-Family and bla OXA-1 , which are commonly found on the same plasmid ( Livermore et al., 2019 ), for the most part had values that ranged between 1% (-1) and 10% (-2) of the total bacterial population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations